2000
DOI: 10.1046/j.1440-1819.2000.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal order of sleepiness, performance and physiological indices during 19‐h sleep deprivation

Abstract: Nineteen-hour variation of subjective sleepiness, performance and physiological indices were assessed during sleep deprivation. Longitudinal data of each index had its characteristic curve through which the values changed from day level to night level. A comparison of the time when each curve crossed its mid-range (50% value of its range) showed that those of subjective sleepiness and heart rate were significantly earlier than those of tracking error and coefficient of variation of R-R interval (CV R-R ), P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The AAT method is excellent, because it differs from the conventional MSLT which is needed various experiment conditions and the point that objective wakefulness level can be presumed in a short time and by easy technique. Moreover it is suggested that AAT is based on the physiological phenomenon in which if sleepiness increases alpha wave decrease in closed eyes condition and increases in opened eyes condition, and also AAT have high sensitivity to the degree of awakening [18][19][20][21] . Therefore, AAT method would be suitable as an index which measures an wakefulness level by whole-body vibration exposure in a short-period, because it can measure in a short time and there is little pain to a subjections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAT method is excellent, because it differs from the conventional MSLT which is needed various experiment conditions and the point that objective wakefulness level can be presumed in a short time and by easy technique. Moreover it is suggested that AAT is based on the physiological phenomenon in which if sleepiness increases alpha wave decrease in closed eyes condition and increases in opened eyes condition, and also AAT have high sensitivity to the degree of awakening [18][19][20][21] . Therefore, AAT method would be suitable as an index which measures an wakefulness level by whole-body vibration exposure in a short-period, because it can measure in a short time and there is little pain to a subjections.…”
Section: Discussionmentioning
confidence: 99%
“…EEG was measured using an electroencephalograph (Nihon Kohden; Neuropack Four, Japan), and after FFT treatment (1 section 4-s, 100 Hz of sampling frequencies) using the [18][19][20][21][22][23] . When the power spectrum of alpha-wave becoming large during closed eyes, if a wakefulness level is high, blocking becomes remarkable during opened eyes and the power spectrum of alpha-wave decreases sharply.…”
Section: Methodsmentioning
confidence: 99%
“…That increased physiological sleepiness can cause impaired psychomotor performance has been shown in human extended-wakefulness studies (De Gennaro et al, 2001;Nakano et al, 2000;Thomas et al, 2000), shift-work model (Porcu et al, 1998), a clinicopathologic survey for disorders characterized by excessive daytime sleepiness (Cohen-Zion et al, 2001;Hood and Bruck, 1996;Kinnari et al, 2000;Schulz et al, 1997), and a clinicopharmacological survey of alertness-modifying drugs such as caffeine, modafinil, and melatonin (De Valck and Cluydts, 2001;Nave et al, 2002;Wesensten et al, 2002). Although it remains unclear whether impaired psychomotor performance after DZP administration could also be caused by increased sleepiness, the magnitude of heat loss induced by Bz agonist may be a potent indicator to predict sedative effects on brain function.…”
Section: Commentmentioning
confidence: 93%
“…Recent studies have shown that the sleep-producing mechanism in humans is preceded by increased heat loss (Campbell and Broughton, 1994;Gilbert et al, 1999;Krauchi et al, 1999Krauchi et al, , 1997 and that various sleep-producing manipulations act, at least in part, by enhancing the heat loss mechanism (Deacon et al, 1994;Dorsey et al, 1999;Gilbert et al, 1999;Krauchi et al, 1999). Furthermore, physiological sleepiness has been shown to cause a decrease in psychomotor performance (De Gennaro et al, 2001;De Valck and Cluydts, 2001;Hood and Bruck, 1996;Kinnari et al, 2000;Nakano et al, 2000;Nave et al, 2002;Porcu et al, 1998;Schulz et al, 1997;Thomas et al, 2000;Wesensten et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In general, adaptation to the lagging of the sleep-wakefulness rhythm, to the shorter and longer day, does not occur. In contrast to day-shift work, it has been shown that performance errors by night-shift workers typically occur in the early morning (Nakano et al, 2000).…”
Section: Risk Factorsmentioning
confidence: 99%